IPGKIK elective music course students' perception towards learning recorder playing / Peter Ong, Rozaina Abd Razak and Fauzila Abdul Latif - Ong, Peter; Abd Razak, Rozaina; Abdul Latif, Fauzila (College of Creative Arts, 2024)
The objective of this study is to evaluate the perception of non-music-oriented students who were enrolled in the IPGKIK optional music course, specifically in relation to their experiences with learning to play the recorder. The aforementioned students are currently enrolled in the first semester of their fourth year. The course is titled "Fun With Music" (DHMK3013). The study utilised a qualitative research methodology, employing structured interviews as the primary technique of data collection. A semi-structured interview protocol consisting of five structured questions was used to conduct interviews with a total of fifteen participants from the Teachers' Training Institute, namely from the Campus Ilmu Khas located in Kuala Lumpur. The consensus among all participants of the course was that the course was effectively executed. The results of this investigation revealed that the participants had a positive perception of the recorder playing based on the interview questions: Firstly, the objectives and justifications for enrolling in this course on recorder playing. Secondly, the advantages of acquiring proficiency in recorder playing. Thirdly, the criteria that the participants should be aware of when aiming for success in recorder playing. Fourthly, an overview of recorder playing. Lastly, the art of recorder playing and the gradation of difficulty in acquiring each technique. The findings of this study indicated that the participants held a favourable impression of the activity of playing the recorder.